Role of salvianolic acid B in the treatment of acute ischemic stroke: a systematic review and meta-analysis of animal models - Wang, Jiashan; Su, Pingping; Wan, Chenyu; Xu, Yingqi; Huang, Junyue; Niu, Jianli; Jin, Zhuqing (Frontiers in Pharmacology, 2024)
BackgroundSalvianolic acid B (Sal B) is potentially the most valuable water-soluble active component in Salvia miltiorrhiza. Its chemical formula contains multiple phenolic hydroxyl groups, so it has a strong antioxidant capacity.ObjectiveWe aim to investigate the efficacy and the potential mechanism of Sal B in the treatment of acute ischemic stroke injury.Materials and methodsCNKI, VIP, WanFang, SinoMed, PubMed and Web of Science were searched for all the literature related to Sal B in the treatment of acute ischemic stroke before August 2024. The methodological quality was assessed using an inspection scale combining the CAMARADES checklist and the new STAIR criteria. Data were analyzed using RevMan5.4 software.ResultsA total of 14 articles were included. Sal B could effectively reduce infarct size, neurological deficit score, brain edema index, and brain water content in cerebral ischemic animals. Sal B could not only increase the content of superoxide dismutase (SOD) and decrease the content of malondialdehyde (MDA) to achieve anti-oxidative stress, but also reduce the level of interleukin-1β (IL-1β) protein to achieve anti-inflammatory response, and reduce the number of TUNEL cells to reflect its anti-apoptosis effect. In addition, Sal B can improve energy metabolism by increasing the content of energy charge (EC) and phosphocreatine (PCr), and maintaining ion balance via Na+/K+ ATPase activity, resulting in the neuroprotective effects against acute ischemic stroke injury.ConclusionThis study showed that Sal B could significantly protect against acute ischemic stroke injury, mainly through anti-oxidative stress, anti-inflammatory response, anti-apoptosis, improving energy metabolism, and stabilizing ion balance.